Application of the Cooperative Learning Learning Model to Improve Student Learning Outcomes in Basic Competencies Understanding Occupational Safety and Health and the Environment (K3LH) in Building Work at SMK Negeri 2 Mandrehe for the 2022/2023 Academic - Afrizal May Yudi Gulo; Aprianus Telaumbanua; Yelisman Zebua (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The problem in this study is that the application of the Cooperative learning learning model has not been implemented optimally so that student learning outcomes in the Basic Competencies of Understanding Occupational Safety and Health and the Environment (K3LH) in Building Work do not meet the KKM standard of 70. The purpose of this study: (1) To describes the implementation of the learning process by applying the Cooperative Learning learning model. (2) To find out the increase in student learning outcomes in the Basic Competencies of Understanding Occupational Safety and Health and the Environment (K3LH) in Building Work in Class X DPIB SMK Negeri 2 Mandrehe. This research is Classroom Action Research (CAR). This research was conducted at SMK Negeri 2 Mandrehe with the research subjects being class X students of the Department of Building Modeling and Information Design (DPIB) semester I of the 2022/2023 Academic Year with a total of 12 students. Research instruments (1) Observation sheet, consisting of (a) Student activity observation sheet in the learning process (b) Observation sheet in the learning process of teacher respondents. (2) Student learning outcomes test, and (3) Photo documentation. The results of the study: (1) in the first (first) cycle, the average observation of the learning process (teacher respondents) was 74.99%, (2) the average percentage of observations of students' activeness in the learning process, namely 48.54%, had not reached the target set determined, the average student learning outcomes is 66.89 classified as sufficient category, the percentage of student learning completeness is 41.66%. (2) in cycle II (second) ) the average observation of the learning process (teacher respondents) was 83.92%, (2) the average percentage of observations of students' activeness in the learning process was 812.95% had not reached the target set, the average student learning outcomes, namely 84.19, are classified as good categories, the percentage of student learning completeness is 100%, has reached the set target of 70%. From the research findings above, it can be concluded that applying the Cooperative Learning learning model to the Basic Competencies of Understanding Occupational Safety and Health and the Environment (K3LH) in Building Work can improve student learning outcomes for Class X-DPIB SMK Negeri 2 Mandrehe in the 2022/2023 Academic Year